Phytochemical investigation of polyphenolic compounds for Cirsium vulgare (Savi) Ten. of Ukraine flora - Y. V. Popova; A. V. Мazulin; G. V. Мazulin; Т. V. Оproshanska (Zaporozhye State Medical University, 2016)
Aim. The herbs of Cirsium vulgare (Savi) Ten. of Ukraine flora are perspective for identification and investigation of quantitative analysis of biologically active polyphenolic compounds. Methods and results. Accumulation of flavonoids and hydroxycinnamic acids in herbs of Cirsium vulgare (Savi) Ten. of Ukraine flora have been studied. 14 Flavonoids (up to 2,10+0,11% ) and 8 hydroxycinnamic acids (up to 0,24+0,021% ) have been identified in the herbs of Cirsium vulgare (Savi) Ten. of Ukraine flora by HPLC method on LC-20 Prominence (Shimadzu, Japan). The chromatography column is Phenomenex Luna C18(2), l=250 mm, d=4,6 mm. Basic compounds, which have been identified, are: linarin, luteolin-7-О-β-D-glucopyranoside, apigenin-7-О-β-D-glucopyranoside, apigenin, kaempferol-3-О-methyl ester, hyperoside, luteolin, rutin, quercetin, luteolin-5-О-β-D-glucopyranoside, gispidulin-7-О-β-D-glucopyranoside, chlorogenic acid. Some compounds have been identified for the first time, namely: linarin, kaempferol-3-О-methyl ester, kaempferol-3-О-β-D-glucopyranoside, luteolin-5-О-β-D-glucopyranoside, gispidulin-7-О-β-D-glucopyranoside, neochlorogenic, capftaric, p-cumaric, caffeic, p-oxybenzoic, syringic and protocatechuic acids. Conclusions. The herbs of Cirsium vulgare (Savi) Ten. are perspective as phytochemical preparations. The standardization method of Cirsium vulgare (Savi) Ten. herbs by flavonoids amount, which are luteolin derivatives has been proposed.